Staged tendon grafts and soft tissue coverage - David Elliot (Indian Journal of Plastic Surgery)
The objective of the two-staged flexor tendon method is to improve the predictability of final results in difficult problems dealing with tendon reconstruction. This article reviews the evolution and benefits of this procedure. It also considers the use of the technique to help deal with problems requiring pulley and skin reconstruction simultaneously with re-constituting the flexor tendon system.